The influence of gas metal arc welding on angular distortion of T-joint - Sharif, Nor Afandi (2014)
Gas Metal Arc Welding (GMAW) or gas metal arc welding is one of the joining technologies and widely used in metal fabrication. The quality of a joint is greatly influenced by the selection of parameter setting of GMAW. One of the quality issues faced in welding is angular distortion. This research focused on angular distortion issues due to welding that happened in the car chassis manufacturing process at EPMB Manufacturing Sdn. Bhd. The distortion resulted in high reject and rework rate. Conventional approach to optimize the welding process parameter in solving this issue has yet to result in significant improvement. The aims of this research is to study the relationship of welding speed, welding angle, welding current and the resultant angular distortion using Response Surface Methodology (RSM) approach. The experiment was carried out using welding manipulator (robotic) type AVII V6, OTC DAIHEN. The weld joint consist of SAPH S45C work piece with T joint arrangement and steel electrode as filler. This is in accordance to the welding process set up at EPMB Manufacturing Sdn. Bhd. The angular distortion was measured using Olympus STM stereo measuring microscope and the analysis using RSM approach was done using design expert version 8.0.7. Based on the result, the interaction between welding angle and speed is the most significant factors that influence the angular distortion. The optimum settings to minimize distortion are 169 Amp (welding current), 42.00 mm/s (welding speed) and 41.0° (welding angle).